PENGARUH BUDAYA ORGANISASI DAN IKLIM ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN (STUDI PADA KARYAWAN TJOKRO HOTEL PEKANBARU) - Rebby Ardila E; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine the effect of Organizational Culture and Organizational Climate partially and simultaneously. This study used a questionnaire as a tool for gathering data distributed to 43 respondents to employees at the Tjokro Pekanbaru hotel. The data is then processed using descriptive analysis and statistical analysis using SPSS 25.0 by conducting validity, reliability testing, simple linear regression analysis, multiple linear analysis, determination analysis (R2) and hypothesis testing with t test (partial test) and F test (simultaneous ).The results showed that the first hypothesis testing is organizational culture on job satisfaction, namely t arithmetic (5,680)> t table (2,020), meaning that organizational culture has a significant effect on job satisfaction. The second Organizational Climate is t arithmetic (5,680)> t table (2,020), meaning that organizational climate has a significant effect on job satisfaction. Test results F arithmetic (25,640)> F table (3,230), meaning that organizational culture and organizational climate simultaneously have a significant effect on job satisfaction. Keywords: Organizational Culture, Organizational Climate, Job Satisfaction.